Mandela : a critical life - Lodge, Tom, 1951- (OUP E-Books., 2006)
A new and highly revealing look at one of the most celebrated political figures of our times. Drawing upon a range of original sources, Tom Lodge explores the making of a modern-day political hero, from Mandela's childhood years through to his role as a statesman in the construction of the new South Africa. - ;Nelson Mandela, the first African politician to acquire a world following, remains in the 21st century an iconic figure. But what are the sources of his almost mythic appeal? And to what extent did Mandela self-consciously create the status of political hero that he now enjoys?. This new.